Perceived Impact of Aerobic Exercise on Cardiovascular Health Among Athletes at the University of Ilorin: An Educational Technology Perspective - Bakinde , Surajudeen; Aladesusi, Gboyega (Journal of Physical Education, 2025)
Lifestyle changes through daily exercise are essential for improving health and fitness. Regular physical activity, whether vigorous or moderate, significantly contributes to the overall well-being of individuals. Observations at the University of Ilorin revealed that some athletes experience rapid fatigue due to inadequate cardiovascular health, often leading to early substitutions by coaches. Despite the recognition of physical exercise's value, its application remains largely theoretical rather than practical. This study aimed to investigate the effects of aerobic exercise on the heart rate and blood pressure of athletes at the University of Ilorin, while also exploring the role of educational technology (ET) in enhancing training interventions. An ex post facto research design was employed, encompassing a population of 207 athletes, with a sample of 106 selected via a multi-stage sampling procedure. A validated researcher-structured questionnaire (r = 0.78) served as the data collection instrument. Descriptive statistics were utilized to analyze demographic data, while inferential statistics, including Pearson’s Product Moment Correlation (PPMC), tested the hypotheses at a 0.05 alpha level. The findings indicated a significant relationship between aerobic exercise and both blood pressure (n = 106, r = 0.524, p < 0.05) and heart rate (n = 106, r = 0.443, p < 0.05) among athletes. Additionally, the study highlighted the role of educational technology in providing insights for developing effective training interventions that promote long-term heart health. The study concluded that aerobic exercise positively impacts blood pressure and heart rate, emphasizing the necessity for regular aerobic training in athletes’ programs. It is recommended that athletes collaborate with coaches to create personalized aerobic exercise plans tailored to their specific goals and needs, while integrating educational technology to enhance training outcomes.